‏رسالة مهني بن رحومة قوجة - قوجة, مهني بن رحومة (1906)
الورقة حديثة مسطرة، فيها أثر سائل. في الرسالة مدح للقطب، وبأن المرسِل يفتخر به في جامع الزيتونة، ويحتج به لدى الطاعنين في المذهب، وفيها طلب فتوى في مسألة زوجية، وطلب كتابة حرز، وكذلك طلبه محمد قسام. وتبليغ سلام جماعة الهنتات: محمد قسام، صالح مرمش.
Keywords: Hintati, mosquée al- (Tunis)

Entre la disparition et la survie: le métier de "Dallâl" à Tunis - Glasman, Wladimir (Revue de l'Institut des Belles Lettres Arabes, 1982)
on a Jerban in the Sūq al-Liffa and on the (Ibāḍī) Masjid al-Hintātī there.* On the (decline of the number of) professional hawkers in the markets of Tunis, taking as an example Mohammed Zakri, born at Jerba around 1910, who became a Dallāl in the Sūq al-Liffa in the Medina of Tunis, a domain more or less reserved for Jerban merchants in woolen cloths. The Masjid al-Hintātī is in front of nr. 79 of this Sūq. I visited the mosque end of June 1972. Entering from the Sūq al-Liffa by a staircase, at the first floor to the left there were two rooms, three showers and three toilets; to the right there were two rooms and a kitchen. The mosque was on the second floor (c. 20x16 m.); some three to five years before a courtyard and three rooms had been added to the mosque. Jaʿbīrī 1975, 259: Sūq al-Hintātī nr. 84.
Keywords: Hintati, mosquée al- (Tunis); Monuments -- Djerba